Expression of angiotensin-converting enzyme 2 and proteases in COVID-19 patients: A potential role of cellular FURIN in the pathogenesis of SARS-CoV-2 - Drak Alsibai, Kinan (Med Hypotheses, 2020)
Recently, a mini-review was published in the Medical Hypotheses journal by Usul Afsar entitled 2019-nCoV-SARS-CoV-2 (COVID-19) infection: Cruciality of Furin and relevance with cancer. Previous studies have pointed out that disruption of the proteolytic cleavage of proteins can promote infectious and non-infectious diseases. The last few weeks have been marked by an important revelation concerning the pathophysiology of SARS-CoV-2. This new coronavirus disease (COVID-19) is a highly contagious and transmissible acute respiratory infectious disorder. SARS-CoV-2 is composed of RNA-dependent RNA polymerase and structural proteins including Spike protein (S protein). Interestingly, the FURIN, one of the proproteins of the convertase family, plays a crucial role in the maturation of viral glycoproteins. In addition, many viruses including coronaviruses, exploit FURIN for the activation of their glycoproteins. Recent data indicate that SARS-CoV-2 enters human cells by binding to angiotensin-converting enzyme 2. Subsequently, the S protein is cleaved by transmembrane protease serine 2 with the help of FURIN which facilitates the entry of the virus into the cell after binding. Furthermore, it seems that FURIN is implicated in the pathogenesis of SARS-CoV-2 and potentially in the increased rates of human-to-human transmission.